Serum levels of testosterone and performance of surgical or immunocastrated beef steers - Machado, Diego Soares; Alves Filho, Dari Celestino; Argenta, Flânia Mônego; Brondani, Ivan Luiz; Martini, Ana Paula Machado (Comunicata Scientiae, 2018)
The objective of the present study was to evaluate the serum concentration of testosterone and the performance of beef steers submitted to different surgical or immunological castration strategies. Forty- eight Aberdeen Angus calves were randomly distributed in the following treatments: surgical castrated at birth; surgical castrated at weaning; immunocastrated with three doses of Bopriva® vaccine; immunocastrated with four doses of Bopriva® vaccine. The hormonal dosages were performed through ELISA Test by “In vitro” competition. The weighing and body condition score of the animals were determined at the beginning and at the end of each evaluated phase. The completely randomly experimental design was used. Data were submitted to variance analysis by F test, being the averages compared by Tukey test with α=0.05. There was an interaction between treatment and collection date (P<0.05) for the serum levels of testosterone. By occasion of the slaughter, all the animals presented a similar serum concentration of testosterone, characterizing them as castrated. Animals immunological castrated with three doses of Bopriva® presented higher daily average gain and total weight gain on finishing phase than the ones surgical castrated at weaning. The immunological castration shows a viable alternative in relation to surgical castration.